(3CSGSjGJ GdHQfGeL hjfOhR eY OYe ddZI GdYQHjI (B/s - (3eMeO LeGd CMeO bHjYIs ((3HjQhJ (B:s (3OGQ GdQGJH GdLGeYjI,s, 1994)
(3eG gh hjfOhR(B.s
Keywords: (3eGjcQhShaJ hjfOhR (B((3eda MGShH(B)s; (3fXe GdJTZjd (B((3MGSHGJ EdcJQhfjI(B)s